The therapeutic effect of deep brain stimulation on olfactory functions and clinical scores in Parkinson's disease - Saatçi, Özlem; Helvacı Yılmaz, Nesrin; Zırh, Ali; Yuluğ, Burak (Elsevier Science Ltd, 2019)
Deep brain stimulation (DBS) is still a highly effective treatment option that significantly improves motor function in advanced PD. Moreover, previous findings have shown that Olfactory dysfunction (OD) has been found in a majority of patients with Parkinson's Disease (PD). Despite this, the effect of DBS on the olfactory function is not fully understood. Here we aimed to determine the effect of STN DBS on OD by evaluating the olfactory functions in the preoperative and postoperative early stages (1st and 3rd months) in forty-five PD patients and 40 healthy controls. The therapeutic effect of DBS on the improvement of motor functions was parallelly investigated. We have observed that there was a significant improvement in OI in the 1st month and in all olfactory parameters (OT, ODI, OI, and TDI) in the 3rd month. In evaluating the motor functional scores, we have revealed a statistically significant (p < 0.001) difference between preoperative UPDRS-motor score (23 +/- 7.3) and the postoperative 3rd month score (11.1 +/- 5.1). Although Beck Depression and Anxiety scores were improved to a certain level in the 3rd month, this improvement was not at a statistically significant level (p > 0.05). As a conclusion, we have shown that STN-DBS improves the smell functions in PD within three months suggesting that the therapeutic effects of DBS might have a wide range of therapeutic spectrum. Despite some limitations (i.e., short follow-up period) our study gives a critical message that future studies are needed to evaluate the functional correlates of STN-DBS treatment in PD patients.
Keywords: Deep Brain Stimulation; Parkinson's Disease; Olfactory Dysfunction